2011
DOI: 10.1186/1471-2350-12-169
|View full text |Cite
|
Sign up to set email alerts
|

Detecting 22q11.2 deletion in Chinese children with conotruncal heart defects and single nucleotide polymorphisms in the haploid TBX1 locus

Abstract: BackgroundConotruncal heart defects (CTDs) are present in 75-85% of patients suffering from the 22q11.2 deletion syndrome. To date, no consistent phenotype has been consistently correlated with the 22q11.2 deletions. Genetic studies have implicated TBX1 as a critical gene in the pathogenesis of the syndrome. The aim of study was to determine the incidence of the 22q11.2 deletion in Chinese patients with CTDs and the possible mechanism for pathogenesis of CTDs.MethodsWe enrolled 212 patients with CTDs and 139 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 32 publications
0
24
1
2
Order By: Relevance
“…Most importantly, our data indicate that all cases with the characteristic face exhibited 22q11.2 heterozygous 3-Mb or 1.5-Mb deletion, suggesting that characteristic face that commonly presents in the majority of Caucasian individuals [30] forms an indicative factor for direct diagnosis of 22q11.2 deletions in Chinese VCFS patients. There seems to be a discrepancy between the present study and the study of Xu et al [31], in which some of the 13 Chinese 22q11del patients did not show a characteristic face. This may be explained by that the patients in their study were mostly infants, whose facial characteristics might not have been yet recognizable, i.e., the phenotypes were not manifested yet.…”
Section: Discussioncontrasting
confidence: 99%
“…Most importantly, our data indicate that all cases with the characteristic face exhibited 22q11.2 heterozygous 3-Mb or 1.5-Mb deletion, suggesting that characteristic face that commonly presents in the majority of Caucasian individuals [30] forms an indicative factor for direct diagnosis of 22q11.2 deletions in Chinese VCFS patients. There seems to be a discrepancy between the present study and the study of Xu et al [31], in which some of the 13 Chinese 22q11del patients did not show a characteristic face. This may be explained by that the patients in their study were mostly infants, whose facial characteristics might not have been yet recognizable, i.e., the phenotypes were not manifested yet.…”
Section: Discussioncontrasting
confidence: 99%
“…CTDs are a prominent part of the 22q11DS phenotype, with a frequency of approximately 75% in 22q11DS patients. Reports originating from Western countries associate 12.8-17.8% of CTDs to the del22q11, and our own work showed a lower incidence (6.13%) in Chinese CTDs patients [3]. The TBX1 gene, a member of a phylogenetically conserved T-box gene family of DNA-binding transcription factors, is mapped to the 22q11.2, and is hypothesised to be responsible for the cardiac phenotype of 22q11.2 deletion syndrome.…”
Section: Introductionmentioning
confidence: 87%
“…Two of these genes displaying myogenic hypermethylation, PAX3 (a homeobox gene) and TBX1 (a T-box gene), encode transcription factors involved in various developmental pathways, including myogenesis 17 - 19 17 , 19 , 20 . In tested myogenic hypermethylated sites associated with these genes, we found that skeletal muscle was the only sample enriched in 5-hmC.…”
Section: Introductionmentioning
confidence: 94%